2018
DOI: 10.1002/anie.201712061
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Bifunctional Phosphine‐Carboxylate Ligands for Palladium(0)‐Catalyzed Enantioselective C−H Arylation

Abstract: Previous enantioselective Pd -catalyzed C-H activation reactions proceeding via the concerted metalation-deprotonation mechanism employed either a chiral ancillary ligand, a chiral base, or a bimolecular mixture thereof. This study describes the development of new chiral bifunctional ligands based on a binaphthyl scaffold which incorporates both a phosphine and a carboxylic acid moiety. The optimal ligand provided high yields and enantioselectivities for a desymmetrizing C(sp )-H arylation leading to 5,6-dihyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(29 citation statements)
references
References 54 publications
1
26
0
Order By: Relevance
“…(R)-6-((2'-(Diphenylphosphaneyl)-[1,1'-binaphthalen]-2-yl)oxy)hexanoic acid (L5): Synthesized according to reported procedure. 3 Spectral data are in agreement with reported literature.…”
Section: S7supporting
confidence: 91%
“…(R)-6-((2'-(Diphenylphosphaneyl)-[1,1'-binaphthalen]-2-yl)oxy)hexanoic acid (L5): Synthesized according to reported procedure. 3 Spectral data are in agreement with reported literature.…”
Section: S7supporting
confidence: 91%
“…In contrast to Pd II catalysis, the use of bifunctional ligands in Pd 0 ‐catalyzed C−H activation has remained unknown for a long time. In 2018, our group reported the first example of Pd 0 ‐catalyzed intramolecular C−H arylation using a bifunctional ligand [119] . The design of the latter was based on MOP‐type ligands, [120] with a chiral binaphthyl scaffold substituted on one side with a phosphine and on the other with a carboxylic acid (Scheme 49).…”
Section: Chiral Bases and Bifunctional Ligandsmentioning
confidence: 99%
“…In 2018, our group reported the first example of Pd 0 -catalyzed intramolecularC ÀHa rylation using ab ifunctional ligand. [119] The design of the latter was based on MOP-type ligands, [120] with ac hiral binaphthyl scaffold substituted on one side with ap hosphine and on the other with ac arboxylic acid (Scheme 49). Monofunctional ligandss uch as MOP,a ne stersubstituted MOP (L 33 ), but also other classic chiral ligandss uch as TADDOL-based phosphoramidite L 2 ,B INAP,a nd NHCs, provided lower enantioselectivities in combination with an external carboxylic acid.Further investigations revealed that the distance between the carboxylic group and the binaphthalene scaffold was important fort he enantioselectivity (L 34 -L 36 ), with an optimum for MOP-acetic acidh ybrid ligand L 34 .A dditional adjustments of the phosphorus aryl substituents allowed not only the yield to be improved, but also the enantioselectivity to be increased (L 37 ,e .r.9 7.5:2.5).…”
Section: Bifunctional Ligandsmentioning
confidence: 99%
“…To induce a more organized transition state, and thereby to provide higher enantioselectivities in challenging cases, we recently developed a new family of chiral bifunctional phosphine‐carboxylate ligands (Scheme 1 a). [8] Herein, we describe the application of this approach to the enantioselective synthesis of highly symmetrical fluoradenes, [9] through the selective activation of one enantiotopic C−H bond (Scheme 1 b), and other warped molecules, which could serve to the bottom‐up preparation of buckybowls or other bowl‐shaped hydrocarbons.…”
Section: Methodsmentioning
confidence: 99%